IMPLEMENTASI PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA LEMBAGA PERKREDITAN DESA DI KECAMATAN NUSA PENIDA - Widhiastuti, Ni Luh Putu; Ni Luh Gde Novitasari; Ni Wayan Mita Purnama Sari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This study aims to determine the effect of transparency, accountability, responsibility, independence, and fairness on LPD performance. The population studied were all LPD in Nusa Penida District, there were 46 LPDs. Respondents selected in this study were 138 people consisting of chairpersons, employees, and supervisory bodies from each LPD in Nusa Penida District which were obtained based on non-probability sampling technique with saturated samples. The analysis technique used is multiple linear regression. The results of this study are that all independent variables, namely transparency, accountability, responsibility, independence, and fairness have a positive effect on the performance of the LPD in Nusa Penida District.